2018
DOI: 10.1177/1091581818794455
|View full text |Cite
|
Sign up to set email alerts
|

Safety Assessment of Tocopherols and Tocotrienols as Used in Cosmetics

Abstract: The Cosmetic Ingredient Review (CIR) Expert Panel (Panel) assessed the safety of 14 tocopherols and tocotrienols and concluded these ingredients are safe as used in cosmetics. The tocopherols are reported to function in cosmetics as antioxidants or skinconditioning agents; in contrast, tocotrienols are not reported to function as an antioxidants in cosmetics but as a light stabilizer, oral care agent, or skin-conditioning agent. The Panel reviewed the new and existing animal and clinical data to determine the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 61 publications
1
28
0
Order By: Relevance
“…Splits is the kernel commercial term for the botanical cotyledons. That cotyledons contain more fat than embryos (Uaciquete & Manjate, 2019), explains the high concentrations of tocotrienols, as lipophilic molecules (Fiume et al., 2018), along with fats in splits. The splits also showed higher concentrations of tocotrienols than white wholes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Splits is the kernel commercial term for the botanical cotyledons. That cotyledons contain more fat than embryos (Uaciquete & Manjate, 2019), explains the high concentrations of tocotrienols, as lipophilic molecules (Fiume et al., 2018), along with fats in splits. The splits also showed higher concentrations of tocotrienols than white wholes.…”
Section: Resultsmentioning
confidence: 99%
“…This is the first report showing the profile of specific fatty acid distribution among different commercial cashew kernel grades. Most of the previous publications focused on the cashew kernel in relation to other nuts (Chung et al., 2013; Fiume et al., 2018; Griffin & Dean, 2017) or simply provided the proximate composition (Okonkwo & Ozoude, 2015) or provided profiles in derivatives such as oil (Kosoko et al., 2009; Liu et al., 2019), flour (Emelike et al., 2015; Ogungbenle & Afolayan, 2015) or butter (Jegede et al., 2020). In a preliminary study using the AOAC method (AOCS, 1983), total fat content was found to be significantly lower in BB grade (33.8 versus.…”
Section: Resultsmentioning
confidence: 99%
“…The safety and efficacy of tocotrienols have been clearly demonstrated in various research and reviews, both in human and animal studies (35)(36)(37)(38).…”
Section: Discussionmentioning
confidence: 99%
“…Protective effects of α-TP against cell damage caused by peroxidants and UV irradiation were reported [ 4 6 ]. Synthesized α-TP is used in cosmetics due to its antioxidant and skin-conditioning activities [ 7 ]. The major risk factor for skin cancer in humans is prolonged exposure to UV light from the sun [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%